Effect of Acute Ingestion of Green Tea Extract and Lemon Juice on Oxidative Stress and Lipid Profile in Pigs Fed a High-Fat Diet - Xi Fang; Michael Azain; Kristi Crowe-White; Jennifer Mumaw; Janet A. Grimes; Chad Schmiedt; Michele Barletta; Srujana Rayalam; Hea Jin Park (MDPI AG, 2019)
Green tea and its catechins have been shown to ameliorate high fat diet-induced oxidative stress and hyperlipidemia. However, low bioavailability of catechins limits their therapeutic potential. Lemon juice (LJ) has been suggested to enhance the bioavailability of catechins in vitro. This study investigated the antioxidative and hypolipidemic efficacy of a single dose of green tea extract (GTE) or GTE plus LJ (GTE + LJ) in high-fat diet fed pigs. Sixteen pigs ingested a single dose of GTE (190 mg/kg/day) or GTE + LJ (0.75 mL/kg/day) mixed with low-fat (LF; 5% fat) or high-fat (HF; 22% fat) diets and blood samples were collected for 24 h. Plasma catechin level peaked at two hours, and gradually returned to baseline after six hours following the intake. The addition of LJ significantly increased plasma catechin level. The diet containing GTE did not lower plasma cholesterol and triacylglycerol (TG) concentrations, superoxide dismutase (SOD) and catalase activity, or malondialdehyde concentration in 24 h in HF-fed pigs. Addition of a single dose of LJ, however, significantly decreased plasma TG level in LF groups but did not cause further changes on any other markers compared to the GTE alone. Our findings indicate limited effect of a single meal containing GTE on plasma antioxidant enzymes, lipid profile, and lipid peroxidation in pigs and no significant synergistic/additive action of adding LJ to GTE within 24 h in pigs. A study with a longer treatment period is warranted to further understand the potential role of GTE in reducing HF diet-induced oxidative stress and the possible synergistic role of LJ.